Ceftolozane–tazobactam- and ceftazidime–avibactam-resistant Pseudomonas aeruginosa mastoiditis. Issue 2 (20th February 2020) - Jacobs, Jeremy; Maris, Alexander; Stratton, Charles
Abstract : Pseudomonas aeruginosa is an important bacterial cause of a variety of infections and is associated with high morbidity and mortality. Infections caused by this bacterium are becoming more difficult to treat due to increasing resistance to many of the available antibiotics. Ceftolozane–tazobactam and ceftazidime–avibactam are two new cephalosporin/β-lactamase inhibitor combination antimicrobials that have demonstrated excellent in vitro activity against several multi-drug-resistant pathogens, including multi-drug-resistant P. aeruginosa . Cases of infections with isolates of multi-drug-resistant P. aeruginosa that are resistant to both of these antimicrobials have rarely been reported. We report a case of mastoiditis caused by P. aeruginosa that was resistant to both ceftolozane–tazobactam and ceftazidime–avibactam.